Associations between sexual precedent and sexual compliance: An event-level examination. Issue 1 (14th February 2022) - Willis, Malachi; Fu, Tsung-Chieh (Jane); Jozkowski, Kristen N.; Dodge, Brian; Herbenick, Debby
Abstract: Objective Most studies on agreeing to unwanted sex have assessed sexual encounters between people who have had sex before. Thus, we examined instances of sexual compliance with a novel sexual partner. Participants: A probability sample of college students at a university in the Midwest United States ( N  = 7, 112). Methods: Participants completed an online survey based on measures from the National Survey of Sexual Health and Behavior. Results: Only 2.5% ( n  = 179) agreed to unwanted sexual activity at their most recent sexual encounter. People who were sexually compliant with a novel sexual partner frequently did so due to their own alcohol intoxication. Further, sexual compliance with novel sexual partners was less frequently associated with affectionate sexual behaviors or orgasm. Conclusions: Our initial findings regarding the effect of sexual precedent on sexual compliance warrant further research on instances when people agree to sex they don't want with novel partners.